Long term follow-up of Palivizumab administration in children born at 29–32 weeks of gestation. (April 2019) - Bar-Yoseph, Ronen; Haddad, Julie; Hanna, Monnera; Kessel, Irena; Kugelman, Amir; Hakim, Fahed; Bentur, Lea
Abstract: Background: Severe respiratory syncytial virus (RSV) bronchiolitis requiring hospitalization induces long term immunological and respiratory abnormalities. The long-term immunomodulation effect of Palivizumab (RSV monoclonal antibody) prophylaxis and its impact on the development of asthma remain controversial. Our aim was to evaluate airway hyper-reactivity, systemic inflammatory markers, allergic parameters and respiratory morbidity, 5–7 years following Palivizumab administration to children born at 29–32 weeks of gestation (WGA). Methods: Children born at 29–32 WGA were evaluated at age 5–7 years. Methacholine challenge test (MCT), serum inflammatory cytokines, fractional exhaled nitric oxide (FeNO), blood tests for eosinophil count, IgE and assessment of respiratory morbidity by questionnaire were compared between those born before Palivizumab prophylaxis was extended to 29–32 WGA and those who received Palivizumab prophylaxis. Results: Of 42 children recruited, 27 received Palivizumab and 15 did not. The mean gestational age and weight were lower in the Palivizumab group. Similar values of spirometry, MCT, FeNO and allergic parameters were observed in the two groups. The Palivizumab group had higher IL4, IL5 and IL13 (Th2 cytokines), IL6, IL17α, and G-CSF (Th17 activation), and lower IL12 and higher INF-γ (Th1 cytokines). Conclusion: Compared to children who did not receive immunoprophylaxis, among children who received Palivizumab, no beneficial effects on long-term respiratory morbidity, airway reactivity or allergic parameters were observed, and levels of Th2 and Th17 cytokines implicated in the pathogenesis of asthma were higher. These findings cast doubt on the potential long-term beneficial effect of Palivizumab on asthma inception. Highlights: The long term effect of Palivizumab on children born at 29–32 WGA was assessed. No beneficial effects on respiratory morbidity, AHR or allergic parameters. Levels of Th2 and Th17 cytokines were higher in the vaccinated group. This small study challenges the potential long-term beneficial effect of Palivizumab.